2013
DOI: 10.1089/acm.2011.0404
|View full text |Cite
|
Sign up to set email alerts
|

Does Traditional Chinese Medicine Pattern Affect Acupoint Specific Effect?Analysis of Data from a Multicenter, Randomized, Controlled Trial for Primary Dysmenorrhea

Abstract: It suggested that TCM pattern might affect acupoint specific effect on the immediate pain relief obtained for participants with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Each subsequent treatment session would allow for a confirmation or update on the TCM diagnosis and therefore point selection could vary from treatment to treatment. Multiple patterns of disharmony are common in dysmenorrhea[36] and this trial supported up to two concurrent patterns of disharmony, designated as root (primary) and secondary (branch) patterns. In all cases no more than seven acupuncture points were to be used.…”
Section: Methodsmentioning
confidence: 58%
“…Each subsequent treatment session would allow for a confirmation or update on the TCM diagnosis and therefore point selection could vary from treatment to treatment. Multiple patterns of disharmony are common in dysmenorrhea[36] and this trial supported up to two concurrent patterns of disharmony, designated as root (primary) and secondary (branch) patterns. In all cases no more than seven acupuncture points were to be used.…”
Section: Methodsmentioning
confidence: 58%
“…A few trials reported up to four different rationales. Endorphin-mediated mechanisms were identified in 12 trials, 3,[19][20][21][22]26,[28][29][30]32,34,43 the gate-control theory was reported in eight trials, 19,20,22,34,36,37,42,43 TCM theory was described in six trials, 19,20,27,32,33,43 DNIC in two trials, 30,34 neuroendocrine effect in five trials, 29,32,[39][40][41] placebo effect based on endogenous opioid mechanism in one trial, 28 and long-term depression (LTD) effect in one trial. 28 Six RCTs offered no discernible physiologic rationale.…”
Section: Resultsmentioning
confidence: 99%
“…That is, 23 patients in SP6 acupuncture group, 26 in GB39 control group and 11 in Nonacupoint control group, respectively. The methodology is the same with the main study [14]. …”
Section: Methodsmentioning
confidence: 99%